Physical therapy for injuries of the temporomandibular joint - Kosharna , Anastasiia; Khudetskyy , Igor; Mykhalchenko , Serhii (The Ukrainian Scientific Medical Youth Journal, 2024)
injuries of the temporomandibular joint (TMJ) pose significant challenges to patients' well-being and require comprehensive treatment strategies. Physical therapy has emerged as a vital component in the management of TMJ injuries, with its efficacy increasingly recognized in clinical practice. This review provides a thorough summarize of physical therapy interventions for TMJ injuries, focusing on their role in restoring joint function and improving patient outcomes. Additionally, this review explores emerging trends and future directions in TMJ physical therapy, including advancements in technology and novel treatment modalities. Through a synthesis of current research and clinical evidence, the review explores various physical therapy modalities, including exercises, manual therapy techniques, and patient education programs. Additionally, the review discusses the mechanisms of action underlying physical therapy interventions and their impact on TMJ mobility, pain reduction, and overall quality of life. The relevance of physical therapy in the multidisciplinary approach to TMJ injury management is emphasized, highlighting its potential to complement other treatment modalities such as pharmacotherapy and surgical interventions. Furthermore, the review addresses considerations for optimizing physical therapy protocols, including patient selection, treatment duration, and therapist expertise. Overall, this review underscores the importance of physical therapy in the comprehensive care of TMJ injuries and provides insights into its implementation for clinicians and researchers alike. Considerations for patient-centered care and shared decision-making are also addressed, recognizing the importance of individualized treatment plans tailored to patient preferences and goals. By providing a comprehensive overview of physical therapy for TMJ injuries, this review aims to inform clinicians, researchers, and policymakers about the evolving landscape of TMJ management and promote evidence-based practice for improved patient outcomes and quality of life.